Analysis of Public Perception in Jayapura Regency Towards The Implementation of Online Public Services by The Jayapura Regency Government, Papua Province - Zumrotun, Fika; Kameo, Daniel D.; Marwata, Marwata (Sahabat Publikasi, 2025)
The implementation of online public services by the Jayapura Regency Government was expected to improve licensing processes by enhancing speed, transparency, and efficiency. However, challenges persist, particularly in remote areas where internet access and digital literacy are limited. This study aims to assess public perception regarding the online licensing services provided by the Jayapura Regency Government and identify the factors affecting service quality. A qualitative approach was used, involving interviews, observations, and document analysis. Key informants, including service users and officers from the DPMPTSP office, were engaged to explore their experiences with online licensing services. The study found that service quality has declined, as indicated by low satisfaction levels among applicants. Issues such as inadequate officer responsiveness, poor communication, lack of infrastructure, and slow internet connectivity were identified as key barriers. Additionally, the absence of prior socialization about the online system further hindered the public’s ability to understand licensing requirements. The research highlights the need for improved training for service officers, better infrastructure, and enhanced community outreach to increase the effectiveness of online licensing services. Addressing these issues is essential for achieving the objectives set by the central government and improving service delivery in Jayapura Regency.